Deposition of Highly Porous Nanocrystalline Platinum on Functionalized Substrates Through Fluorine‐Induced Decomposition of Pt(PF3)4 Adsorbates. (5th June 2013) - Randolph, Steven J.; Botman, Aurelien; Toth, Milos
<x xml:space="preserve">Abstract</x> Nanocrystalline platinum is synthesized at room temperature by co‐injecting Pt(PF3)4 and XeF2 vapors onto solid supports in vacuum. The Pt nucleation time scales with chemisorbed fluorine coverage, which is controlled by pre‐dosing supports with XeF2, and by optional electron or ion beam irradiation under flowing XeF2. The latter is used to increase the chemisorbed fluorine coverage and localize the Pt growth process. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>